Investigation into the participation of students with disabilites in HIV and AIDS programmes at the University of Johannesburg - Ramafola, Pearl Berlinda (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.